2021
DOI: 10.3390/cancers14010168
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free-DNA-Based Copy Number Index Score in Epithelial Ovarian Cancer—Impact for Diagnosis and Treatment Monitoring

Abstract: Background: Chromosomal instability, a hallmark of cancer, results in changes in the copy number state. These deviant copy number states can be detected in the cell-free DNA (cfDNA) and provide a quantitative measure of the ctDNA levels by converting cfDNA next-generation sequencing results into a genome-wide copy number instability score (CNI-Score). Our aim was to determine the role of the CNI-Score in detecting epithelial ovarian cancer (EOC) and its role as a marker to monitor the response to treatment. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Cancer detection and minimal residual disease monitoring via circulating tumour DNA has increasing applications across tumor indications. Recently, Braicu and colleagues ( 6 ) provided proof-of-concept evidence to detect HGSC in a prospective cohort ( n = 109) in comparison to healthy controls ( n = 241) by copy-number index score (CNI-Score) from ctDNA. Together with the conclusions of Cheng and colleagues ( 1 ), the need for high-sensitivity detection of chromosomal alterations and WGD will need to be incorporated into ctDNA detection algorithms for HGSC.…”
mentioning
confidence: 99%
“…Cancer detection and minimal residual disease monitoring via circulating tumour DNA has increasing applications across tumor indications. Recently, Braicu and colleagues ( 6 ) provided proof-of-concept evidence to detect HGSC in a prospective cohort ( n = 109) in comparison to healthy controls ( n = 241) by copy-number index score (CNI-Score) from ctDNA. Together with the conclusions of Cheng and colleagues ( 1 ), the need for high-sensitivity detection of chromosomal alterations and WGD will need to be incorporated into ctDNA detection algorithms for HGSC.…”
mentioning
confidence: 99%
“…CNV analysis indicated that hyperploid cells enriched tumor metastasis and chemoresistance in ovarian cancer [21][22][23]. The analysis of cell-free DNA or circulating-tumor DNA supports the value of aneuploidy in the monitoring of tumor progression, therapeutic efficacy and tumor recurrence [24,25]. Overall, as a genetically unstable tumor, aneuploidy and chromosomal instability are prevalent and dynamic in ovarian cancer patients.…”
Section: Introductionmentioning
confidence: 72%
“…Chromosomal instability is a source of a disturbed copy number state, which is detectable in the ctDNA test. The copy number instability score (CNI-score) reached a sensitivity of 91% and a specificity of 95% to detect ovarian cancer in blood samples [237].…”
Section: Biomarkermentioning
confidence: 99%
“…Improved malignancy detection (AUC 0.94) compared to CA125 (AUC 0.78) and RMI index (AUC 0.81) [191] NIPT sequencing Detected 41% of all HGSOC, including 38% of early-stage cases [236] CNI-score A sensitivity of 91% and a specificity of 95% to detect ovarian cancer in blood samples [237]…”
Section: Chromosomal Instabilitymentioning
confidence: 99%